Clonidine Versus Midazolam Premedication and Postoperative Negative Behavioral Changes in Younger Children: A Randomized Controlled Trial. (24th February 2022) - Zickerman, Caroline; Hult, Ann-Catrin; Hedlund, Lars; Winsö, Ola; Johansson, Göran; Haney, Michael
Abstract : BACKGROUND: Postoperative negative behavioral changes (NBCs) are common among children, but risk for this is thought to be reduced with premedication. Midazolam has for many years been a standard premedication for children. More recently, the alpha-2 adrenergic agonist clonidine has also become popular as a preanesthetic sedative. We hypothesized that clonidine was superior to midazolam for limiting new NBCs in children as assessed using the Post Hospital Behavior Questionnaire (PHBQ). METHODS: This was a prospective, randomized, controlled, blinded study, including 115 participants aged 24 to 95 months and their parents. The participants underwent ear, nose, or throat outpatient surgery and were randomly allocated to premedication with oral midazolam 0.5 mg/kg or oral clonidine 4 µg/kg. Participants were anesthetized by protocol. At home, later, parents were asked to complete the PHBQ assessment instrument for postoperative NBCs for the participants 1 week, 1 month, and 6 months after the surgery. A secondary outcome, preinduction anxiety, was assessed using modified Yale Preoperative Anxiety Scale (mYPAS). RESULTS: The primary outcome, more than 3 NBCs in an individual case at 1 week, showed no difference in proportions between treatment in the clonidine group compared to the midazolam group, (12/59 or 20% vs 7/56 or 13%, respectively, odds ratio 1.39, 95% confidence interval [CI], 0.75–2.58; P = .32). A secondary result showed a higher preinduction anxiety level in the clonidine compared to the midazolam group (mYPAS >30, 43/59 or 71% vs 12/56 or 21%, respectively; P < .001). CONCLUSIONS: These results did not show a clinical or statistically significant difference, with respect to the primary outcome of behavior changes at 1 week, between the cohorts that received midazolam versus clonidine as a premedication. Abstract :